Geometridae (Lepidoptera) of the Baikal region: identification keys and annotated catalogue with notes to DNA barcoding. Part 2. Archiearinae, Geometrinae, Sterrhinae - Makhov, Ilya (Zootaxa, 2023)
Dichotomous keys to 19 genera and 67 species of Archiearinae (2 genera, 3 species), Geometrinae (9 genera, 14 species) and Sterrhinae (8 genera, 50 species) of the Baikal region (Irkutskaya Oblast and Buryatia, Siberia) are given. The annotated catalogue including synonyms, the details of examined specimens, data on distribution and foodplants with references is provided. Distribution of Comibaena amoenaria (Oberthür, 1883) and Idaea falckii (Hedemann, 1879) in China is established. Lectotypes are designated for Hemistola zimmermanni and Hemistola intermedia Djakonov, 1926. Hemistola intermedia is synonymized with H. zimmermanni (syn. n.). Some taxonomic aspects of Hemistola zimmermanni (Hedemann, 1879), Idaea dohlmanni (Hedemann, 1881), Rhodostrophia jacularia (Hübner, [1813]) and Timandra griseata W. Petersen, 1902 are discussed. Results of DNA barcoding of ten species (Comibaena amoenaria (Oberthür, 1880), Hemistola zimmermanni, Thalera chlorosaria (Graeser, 1890), Chlorissa obliterata (Walker, 1863), Cleta jacutica Viidalepp, 1976, Idaea dohlmanni (Hedemann, 1881), Scopula agutsaensis Vasilenko, 1997, S. impersonata Walker, 1861, S. immutata (Linnaeus, 1758) and Scopula ornata (Scopoli, 1763)) are considered. Three cases of misidentifications and an erroneous association of species and its genitalia illustration in the public sources are recognized and corrected.